SYARAT RASIONAL-OBJEKTIF RAGAM BAHASA ILMIAH: Prinsip Dasar dan Ilustrasi - D. Jupriono; Sudarwati Sudarwati; Susie Chrismalia Garnida (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
The incoherence of sentences in scientific manner occurs due to habits that are repeated from generation to generation. The confusion of thinking results in inaccurate arrangement of sentence structures and this inaccuracy creates illogical meaning of sentences. The objectivity of a sentence will be hurt if the writer presents factual information, but does not have urgency and relevance. Parties in Indonesia who are often victims of language objectivity are subalternan groups, in this case women, families of political prisoners, and racial minorities.